Human and camelid paleodiets in El Bolsón valley (NW Argentina): A stable isotope approach - Neveu Collado, Camila; Killian Galván, Violeta Anahí; Mondini, Nora Mariana; Korstanje, María Alejandra (John Wiley & Sons, 2023)
This study aims at reconstructing Late Holocene human paleodiets in the Andean ElBolsón valley, Catamarca, Argentina, as well as that of camelids –their staple animalresource– as a way of exploring variations in the strategies and patterns of foodprocurement, production, preparation and consumption by local agricultural-pastoralistsocieties. To that aim, we present the first results systematically obtained of carbon( 13 C/ 12 C) and nitrogen ( 15 N/ 14 N) isotopic relationships as measured on camelid andhuman bone collagen. They come from five camelid individuals from Los Viscosarchaeological site, dating to the last 1200 years, and from six human individuals fromarchaeological rescues and isolated finds, as no other human samples have beenobtained in the area. The results suggest that camelids consumed predominantly C 3pastures, locally available, while human paleodiet would have been dominantly C 4 , inwhich camelid protein from Los Viscos was not central. Here we discuss how localproductive strategies played a part in the selective diet of the human inhabitants, andcontextualize this in the larger area comprising the Andean valleys of NW Argentina.